2018
DOI: 10.1108/jm2-02-2018-0029
|View full text |Cite
|
Sign up to set email alerts
|

Application of rough set and netnography in tourism marketing analysis

Abstract: Purpose Social media has given customers more power over sharing their knowledge, opinions and experiences with each other. Tourists as customers of destinations are also using text ads on social media and websites to share their experiences. The purpose of this study is to find out the factors which have affect on the decisions of tourists towards the most popular destinations in Tehran, Isfahan and Shiraz of Iran. Design/methodology/approach Netnography methodology has been applied to 2,852 comments showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The scope that certainly belong to the desired collection in defined as low approximation and the scope that can't certainly belong to the desired collection is defined as upper approximation. Equations ( 3) and ( 4) showed lower and upper approximations (Sajjadian et al 2018):…”
Section: Rough Set Theorymentioning
confidence: 99%
“…The scope that certainly belong to the desired collection in defined as low approximation and the scope that can't certainly belong to the desired collection is defined as upper approximation. Equations ( 3) and ( 4) showed lower and upper approximations (Sajjadian et al 2018):…”
Section: Rough Set Theorymentioning
confidence: 99%
“…If α ( X ) = 1, the set X is considered as a crisp. In other words, if the number is less than 1, the set is a rough set (Sajjadian et al , 2018).…”
Section: Rough and Grey Set Theorymentioning
confidence: 99%
“…Based on the rough set theory, this research proposes an algorithm with related concepts. Sajjadian et al (2018) based on the rough set theory have found that beauty, cultural attractions, safety, welfare, costs and dealing with passengers are the factors affecting consumer behavior in the tourism industry. Sajjadian et al (2018) only used the rough set theory to discover the rules; however, the ranking data have not been further explored.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sajjadian et al (2018) based on the rough set theory have found that beauty, cultural attractions, safety, welfare, costs and dealing with passengers are the factors affecting consumer behavior in the tourism industry. Sajjadian et al (2018) only used the rough set theory to discover the rules; however, the ranking data have not been further explored. Therefore, the research based on the rough set theory presents a new algorithm to deal with ranking data for decision-makers to make decisions while planning a suitable restaurant for dining.…”
Section: Literature Reviewmentioning
confidence: 99%